2010
DOI: 10.4276/030802210x12918167234163
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of the Comparative Analysis of Performance — Motor (CAP-M) for Children with Cerebral Palsy

Abstract: Background and aim: The focus of upper limb assessment for people with neurological damage has expanded beyond impairment factors. Assessments that evaluate the impact of impairment factors within tasks are needed to ensure that interventions address task performance. The Comparative Analysis of Performance-Motor (CAP-M) identifies upper limb impairments during performance of a client-chosen occupational task and uses this information to guide goal formulation. This study investigated the clinical utility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Participation refers to involvement in life situations (problems are termed restrictions), while activity refers to the execution of tasks (problems are termed limitations). However, rather than just gathering information within different levels of function, it is suggested that the critical component of assessment is linking this information across levels, so that it is clear how impairment factors are contributing to activity limitations and participation restrictions [6,7]. An important aspect of the ICF has been its influence on the development of assessment tools that measure activity and participation [2,3].…”
Section: The Icf As An Assessment Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Participation refers to involvement in life situations (problems are termed restrictions), while activity refers to the execution of tasks (problems are termed limitations). However, rather than just gathering information within different levels of function, it is suggested that the critical component of assessment is linking this information across levels, so that it is clear how impairment factors are contributing to activity limitations and participation restrictions [6,7]. An important aspect of the ICF has been its influence on the development of assessment tools that measure activity and participation [2,3].…”
Section: The Icf As An Assessment Frameworkmentioning
confidence: 99%
“…However, rather than just gathering information within different levels of function, it is suggested that the critical component of assessment is linking this information across levels, so that it is clear how impairment factors are contributing to activity limitations and participation restrictions [6,7]. Linking information across the activity, participation and body structure/function levels can therefore guide the second purpose of assessment, namely, forming an intervention plan that addresses activity and participation directly, and that also targets impairment factors which are limiting activity and participation [6,12,13]. For example, impairments such as spasticity, muscle tone, stiffness and reduced ROM were found to be significantly correlated with scores on the Action Research Arm Test (ARAT), an upper limb activity measure [8,9].…”
Section: The Icf As An Assessment Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes may interfere with activities, including reaching, touching, manipulating, walking, writing, playing, etc. which are required for these children to function both at home and school (Beckung & Hagberg, 2002; Rae, Copley, & Ranka, 2010).…”
Section: Introductionmentioning
confidence: 99%